2013
DOI: 10.1590/s0100-29452013000300021
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização física e química, fenólicos totais e atividade antioxidante da polpa e resíduo de gabiroba

Abstract: PHYSICAL AND CHEMICAL CHARACTERIZATION, TOTAL PHENOLICS AND ANTIOXIDANT ACTIVITY OF THE GABIROBA PULP AND RESIDUEABSTRACT -The Brazilian Cerrado has a wide range of fruit species that have not been sufficiently studied regarding their physical, chemical and functional characteristics. This study aimed to measure the physical characteristics of gabiroba tree's fruits and analyze the proximate and mineral compositions, total phenolic content and antioxidant activity of the gabiroba pulp and residue. The physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
2
18

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 21 publications
2
12
2
18
Order By: Relevance
“…Fruit weight was the characteristic that presented the highest CV, corroborating with the results found in this study. In contrast, the mean and maximum values for fruit weight, diameter and width were lower than those reported by Oliveira et al (2011) and Alves et al (2013), evidencing that the collection under study has a variability for these traits and can thus establish a selective process according to the interest in standardization and generation of a new cultivar.…”
Section: Resultscontrasting
confidence: 63%
“…Fruit weight was the characteristic that presented the highest CV, corroborating with the results found in this study. In contrast, the mean and maximum values for fruit weight, diameter and width were lower than those reported by Oliveira et al (2011) and Alves et al (2013), evidencing that the collection under study has a variability for these traits and can thus establish a selective process according to the interest in standardization and generation of a new cultivar.…”
Section: Resultscontrasting
confidence: 63%
“…In a study of optimization for extraction of bioactive compounds in gabiroba, pitanga-do-cerrado (Eugenia punicifolia) and pêra-do-cerrado (Eugenia klostzchiana) phenolic compounds indices of 385, 364, and 271 mg GAE per 100 g, respectively, were reported (Rocha et al, 2011). Alves, Alves, Fernandes, Naves, and Naves (2013) performed extraction in methanol, and reported that fruits of gabirobeira had an average value of 1222 mg GAE per 100 g. In addition, Lima, Castro, Sabino, Limas, and Torres (2016) reported indices of 229 and 511 mg GAE per 100 g for yellow gabiroba (Campomanesia lineatifolia) and myrtle (Blepharocalyx salicifolius), respectively. Infante, Rosalen, Lazarini, Franchin, and Alencar (2016), in tests of fruits from the genus Eugenia, reported levels of 151, 183, 266 and 178 mg GAE per 100 g for araçá-pitanga (Eugenia leitonii), cherrygrove, grumixama (Eugenia brasiliensis) and pessegueiro-do-mato, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Portanto, entre os extratos estudados, o extrato hidro alcoólico foi mais eficiente na extração dos fenólicos tanto na casca quanto na polpa, e o extrato aquoso foi mais eficiente na extração dos fenólicos na semente. Resultado superior ao encontrado para polpa de gabiroba, foi Mendes et al, v.11, n.39, p. 68-72, Dourados, 2018 relatado por Alves et al (2013), sendo 1.222,59 mg AGE.100g-1 . Segundo, Martins et al (2011) a concentração de compostos fenólicos de um alimento pode variar conforme as condições geográficas e ambientais da região de origem e os fatores fisiológicos e genéticos da planta.…”
Section: Resultsunclassified
“…, na região de Barra doMendes et al, v.11, n.39, p. 68-72, Dourados, 2018 Garças, MT, e superior aos 3,06 g encontrados porAlves et al (2013), na região central do Estado de Goiás. De acordo comSilva et al (2012) variações em frutos do Cerrado são bastantes comuns, devido as espécies ainda não serem domesticadas, assim fazendo com que haja variação entre as matrizes para características como coloração, tamanho e peso.…”
unclassified
See 1 more Smart Citation